Islamic Law for the Colonists: Muftis in Nineteenth- Century British India - Wright, Brian (Islamic Studies, 2019)
This paper is an exploration of the role of the Muslim law officer, or Mufti, in the legal system of British India. Using 400 cases of homicide adjudicated in the courts of Bengal and the Northwestern Provinces from January 1853 to December 1854, the paper argues that Muftis utilised the Islamic concept of siyasah to adapt Islamic jurisprudence regarding the establishment of intent and the categorisation of punishment. This was done to both accommodate overlapping British understandings of the law and ensure that criminals were punished according to shifting conceptions of justice during the nineteenth century.